Educational Governance And Management In Man Binjai - Putra, San; Rahman, Arif; Siagian, Maslina; Karo Karo, Jamal Thahir (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Many schools use School Based Management to manage and administer the education system. One that uses this is MAN Binjai. This management is carried out as a form of educational focus in schools in order to manage school needs in accordance with the environmental conditions of each school. MAN Binjai implements School Based Management in the management or operations of its schools. This research is a type of qualitative research using the case study method using observation, interview and documentary data collection techniques. The research was carried out using data validity tests which include reliability tests, transferability tests, durability tests and confirmatory tests. The research results show that the implementation of school management takes place through the application of school management principles. The principle of independence arises in giving schools the right to organize and manage the economy independently or without other parties. The principle of partnership occurs when a school collaborates with various parties to get support for its programs. The principle of participation is proven by the active participation of stakeholders in the decision-making and policy-making process. Based on the research results obtained, MAN Binjai implements School Based Management by applying 3 principles, namely the principle of independence, the principle of cooperation and the principle of parental participation.